1975
DOI: 10.1177/000348947508400401
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Aural Cholesteatoma Causing Bone Resorption

Abstract: A series of experiments were carried out on 55 guinea pigs in four groups to study the conditions fostering bone resorbin epidermal cysts. The first group had free grafts of canal wall skin applied to the cochlea with and without talc application. The second group had canal skin flaps applied to the cochlea with and without subsequent talc application. The third group had talc applied either to the tympanic membrane or on the cochlea. The fourth group had a canal skin flap inserted into a mucosal pocket in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…Based on Lazarus et al 24 findings that stated that the chemical activity of the perimatrix had a role in bone absorption, Gantz et al 25 demonstrated that inflammatory mononuclear cells produce collagenolytic enzymes. The importance of the perimatrix in bone reabsorption is also pointed out by Abramson et al 26 and it is the first to suggest that the potential of infiltration of cholesteatoma would be related with chemoenzymatic activity of perimatrix.…”
Section: Lim and Saundersmentioning
confidence: 73%
“…Based on Lazarus et al 24 findings that stated that the chemical activity of the perimatrix had a role in bone absorption, Gantz et al 25 demonstrated that inflammatory mononuclear cells produce collagenolytic enzymes. The importance of the perimatrix in bone reabsorption is also pointed out by Abramson et al 26 and it is the first to suggest that the potential of infiltration of cholesteatoma would be related with chemoenzymatic activity of perimatrix.…”
Section: Lim and Saundersmentioning
confidence: 73%
“…33 On the other hand, Harris found few osteoclasts in cholesteatoma lesions. 34 This negative result on the occurrence of osteoclasts was confirmed in the 1970-1980s by a number of studies, [35][36][37][38][39][40][41][42][43][44][45] while only a few reports have supported the presence of osteoclasts in cholesteatoma. 46 These lines of evidence indicate that the presence and participation of osteoclasts in cholesteatoma lesions remain controversial and unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Enzymes appear to digest collagen and demineralize the bone. 11 More typical is a pushing border with a lateral semicircular canal fistula that allows matrix removal. Extensive cholesteatomatous involvement of the labyrinth has been previously reported.t-s In extensive erosion of the otic capsule, large areas are typically dissolved over a broad front of disease.…”
Section: Tabulated Data Resultsmentioning
confidence: 99%